Detection of Fracture Zones for Groundwater Investigation from Interpretation of VLF-EM Anomalies of Kwara State Polytechnic Ilorin and its Environs (Global Journal of Human-Social Science, 2019)
The Very Low Frequency Electromagnetic VLF-EM geophysical methods have been used to map selected settlements in Kwara State Polytechnic Permanent Site and its environs Ilorin Northcentral Nigeria with a view to determine the groundwater potential of the area A total of thirteen 13 profiles were covered during VLF data collection with 20m sample interval along each profile with spread length of between 100m The VLF data were collected using ABEM WADI instrument The data were interpreted using KHFFILT software The qualitative interpretation of the acquired VLF EM data identified areas of hydro-geologic importance The results further showed that the EM anomalies vary greatly Some of the anomaly peaks are narrow and sharp while others are broad with varying width extent The values of the filtered real range from -0 9 to 22 5 across the study area The study area is adjudged based on the VLF data interpretation which indicates the presence of interconnected fracture zones to have potentially good prospects for groundwater development while recommendation is made for further geophysical methods to be employed in order to detect suitable locations for productive and sustainable borehole
Keywords: very low frequency –electromagnetic (VLF-EM); moro lga; abem wadi; em anomalies; fracture zones; groundwater